HOW INTERACTIVITY OF INSTAGRAM ADS THROUGH HEDONIC MOTIVATION CAN AFFECT PURCHASE INTEREST - Mustikasari, Ati; Thaha, Abdurrahman Rahim; Wulandari, Astri (Universitas Brawijaya, Indonesia, 2022)
As the number of internet users and social media users grows, it has a beneficial influence on businesses in attracting various types of business possibilities to market and launch their products via the internet or social media. Instagram is a social network frequently used by businesses in Indonesia to launch, advertise, and update their customers about their products. The Instagram advertising function can give a new option for businesses to help sell their products. This study aimed to determine the effect of interactivity on advertising on social media Instagram through hedonic motivation on consumer purchase intention in the Bandung. The quantitative research approach utilized the SEM (Structural Equation Model) analytical methodology and SmartPLS software. This study's participants were 400 Instagram social media users in Bandung who had viewed advertising presented on Instagram. According to the findings of this study, the interaction that comes from advertising material via hedonic motivation has little influence on the purchase intention of Instagram users who have seen commercials promoted in Bandung. Further researchers can add more unknown factors to determine the impact of interaction on customer purchase intention in Instagram advertising via hedonic motivation. Furthermore, other researchers can do the same research but with other research objects, and the findings can be utilized to compare with this research.